(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the rate of stress level of nursing students at Da Nang University of Medical Technology and Pharmacy and some influencing factors. Method: Cross-sectional study on 510 nursing students at Da Nang University of Medical Technology and Pharmacy. Stress assessment using DASS-21 scale. Results: The rate of stress in students is 53.1%. Of which, mild, moderate, severe, and very severe stress are respectively at the rate of: 18.4%, 18.8%, 11.6%, 4.3%. Influencing factors to stress include: living conditions, perceived health status, frequency of exercise, parents’ marriage, and satisfaction with the major (p<0.05). Conclusion: Stress is a common condition in nursing students. Students need to build positive relationships and participate in physical exercise to improve physical and mental health. Besides, the lecturers and universities need to focus on the issue of career inspiration for students.